KEPEMIMPINAN KEPALA SEKOLAH, KUALITAS PELAYANAN SEKOLAH, DAN PRESTASI UASBN SD DI KOTA MANADO - Esther.E. Undap Palit (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2011)
Abstract: This study had objective to test a relationship between leadership of school principle, schools'service quality, and achievement of the national standardized test in the Manado City elementary schools. The samples were 40 of 264 elementary schools taken by proportional random sampling.The research concluded that there were: (1)  a positive correlation between the leadership of schools' principle and the achievement of the achievement of the national standardized test in the Manado City elementary schools; (2) a positive correlation between  schools' servive  quality and achievement of the national standardized test in the Manado City elementary schools; (3) a positive correlation amongbetween leadership of school principle, schools'service quality, and achievement of the national standardized test in the Manado City elementary schools.Therefore, based on the result of the study, the achievement of the national standardized test in the Manado City elementary schools school can be improved through the leadership of school principle, and school quality of service.   Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan antara kepemimpinan kepala sekolah dan kualitas pelayanan sekolah dengan prestasi Ujian Akhir Sekolah Berstandar Nasional (UASBN) Sekolah Dasar di Kota Manado. Sampel diambil 40 dari 264 SD berdasarkan random sampling proporsional. Hasil penelitian menunjukkan (1) ada korelasi positif antara kepemimpinan kepala sekolah dengan prestasi UASBN, (2) ada korelasi positif antara kualitas pelayanan sekolah dengan prestasi UASBN, dan (3) ada korelasi positif antara kepemimpinan kepala sekolah dan kualitas pelayanan sekolah dengan prestasi UASBN. Dapat disimpulkan bahwa prestasi UASBN dapat ditingkatkan melalui kepemimpinan kepala sekolah dan kualitas pelayanan sekolah.